CCAFS-IMPACT Lite Survey Bangladesh, Satkhira District - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
IMPACT lite is a tool, developed by the International Livestock Research Institute (ILRI) that provides a unifying framework for collecting detailed information on farm resources, farm management strategies, farm productivity and household economics at the household-level. The objective of this survey is to capture within-site variability on key livelihood indicators that could be used for a range of analysis including the modelling of impact of adaptation and mitigation strategies on livelihoods, food security and the environment. The survey was carried out in 13 other benchmark sites across East Africa, West Africa, and South Asia. IMPACT Lite data from Satkhira, Bangladesh were collected by IFPRI as part of the IFPRI-CCAFS Gender and Climate Change Survey Data.